Genome-wide association study identifies 32 novel breast cancer susceptibility loci from overall and subtype-specific analyses - Zhang, Haoyu; Ahearn, Thomas U; Lecarpentier, Julie; Barnes, Daniel; Beesley, Jonathan; Qi, Guanghao; Jiang, Xia; O'Mara, Tracy A; Zhao, Ni; Bolla, Manjeet K; Dunning, Alison M; Dennis, Joe; et al. (Nature genetics, 2020)
Breast cancer susceptibility variants frequently show heterogeneity in associations by tumor subtype1-3. To identify novel loci, we performed a genome-wide association study including 133,384 breast cancer cases and 113,789 controls, plus 18,908 BRCA1 mutation carriers (9,414 with breast cancer) of European ancestry, using both standard and novel methodologies that account for underlying tumor heterogeneity by estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 status and tumor grade. We identified 32 novel susceptibility loci (P < 5.0 × 10-8), 15 of which showed evidence for associations with at least one tumor feature (false discovery rate < 0.05). Five loci showed associations (P < 0.05) in opposite directions between luminal and non-luminal subtypes. In silico analyses showed that these five loci contained cell-specific enhancers that differed between normal luminal and basal mammary cells. The genetic correlations between five intrinsic-like subtypes ranged from 0.35 to 0.80. The proportion of genome-wide chip heritability explained by all known susceptibility loci was 54.2% for luminal A-like disease and 37.6% for triple-negative disease. The odds ratios of polygenic risk scores, which included 330 variants, for the highest 1% of quantiles compared with middle quantiles were 5.63 and 3.02 for luminal A-like and triple-negative disease, respectively. These findings provide an improved understanding of genetic predisposition to breast cancer subtypes and will inform the development of subtype-specific polygenic risk scores.
Keywords: mutace; nádory prsu; Female; Genome-Wide Association Study; ženské pohlaví; BRCA1 Protein; lidé; triple-negativní karcinom prsu; Breast Neoplasms; Mutation; genetická predispozice k nemoci; studie případů a kontrol; Linkage Disequilibrium; Genetic Predisposition to Disease; vazebná nerovnováha; Triple Negative Breast Neoplasms; Case-Control Studies; protein BRCA1; celogenomová asociační studie; Humans